(untitled) (Research, Society and Development, 2021)
Rhipicephalus microplus is responsible for considerable economic losses in tropical and subtropical regions. Plant compounds have been utilized as alternative to conventional acaricids. The objective in this study was to evaluate the effects of fixed oils extracted from seeds of Mauritia flexuosa and Mauritiella armata, palm trees typical of the Brazilian Cerrado on tick R. microplus.The fixed oils were used against engorged females and larvae by biocarrapaticidograms and larval mortality by larval pack tests (LPT). Chemical compositions of the oils were evaluated by gas chromatography using an electron impact ionization detector and showed the presence of the compounds: palmitoleic acid, linoleic acid, palmitic acid, and myristic acid. In the biocarrapaticidogram, the oil from M. flexuosa and M. armata at 5% and 10% concentrations showed efficacies > 80%. Regarding the effect of fixed oils from palm trees on R. microplus larvae, mortality above 80% was observed at all concentrations tested.These bioproducts are a promising alternative for controlling this tick and may be adapted into current integrated control methods for cattle farming.